2011
DOI: 10.1097/sla.0b013e3182368f85
|View full text |Cite
|
Sign up to set email alerts
|

Additional Resection of an Intraoperative Margin-Positive Proximal Bile Duct Improves Survival in Patients With Hilar Cholangiocarcinoma

Abstract: Additional resection of a positive proximal (BD(Marg)) , albeit associated with an increased risk of biliary fistula, offers a significant survival benefit and should be attempted whenever possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 26 publications
0
82
1
4
Order By: Relevance
“…Just like the results as reported by Ribero et al63 for their European center, Zhang et al65 demonstrated that additional resection of a positive proximal or distal ductal margin was associated with improved survival after curative‐intent resection in patients with perihilar cholangiocarcinoma (Table 2). They concluded that every attempt should be made to achieve a carcinoma‐negative ductal margin when technically feasible.…”
Section: Outcome Of Additional Resection For Carcinoma‐positive Ductamentioning
confidence: 56%
See 2 more Smart Citations
“…Just like the results as reported by Ribero et al63 for their European center, Zhang et al65 demonstrated that additional resection of a positive proximal or distal ductal margin was associated with improved survival after curative‐intent resection in patients with perihilar cholangiocarcinoma (Table 2). They concluded that every attempt should be made to achieve a carcinoma‐negative ductal margin when technically feasible.…”
Section: Outcome Of Additional Resection For Carcinoma‐positive Ductamentioning
confidence: 56%
“…In contrast, Ribero et al63 reported that additional resection of a positive proximal ductal margin offered a survival benefit in patients with perihilar cholangiocarcinoma. In their study, survival in patients with a negative proximal ductal margin achieved by additional resection was comparable with that in patients with a primary negative proximal margin and was significantly better than that in patients with a positive ductal margin (Table 2).…”
Section: Outcome Of Additional Resection For Carcinoma‐positive Ductamentioning
confidence: 92%
See 1 more Smart Citation
“…25 Ribero et al 26 demonstrated that reresection of positive proximal bile duct margin to gain secondary R0 resection in patients with hilar cholangiocarcinoma improved median OS to a level similar to that of patients who underwent primary R0 resection. However, the success rate of obtaining secondary R0 resection is limited because of procedural difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent report of Ribero et al [81] , in the analysis of 82 cases, the group of patients who had primary R0 was compared with those patients who achieved a secondary R0 after an intraoperative additional resection, and also with the patients who were R1. The 1-, 3-and 5-year survival rates were similar in the groups with primary R0 and secondary R0, but different in R1 patients (5-year survival rate: 50%, 30.8% and 0% respectively).…”
Section: Liver Resection: How Much Is Enough?mentioning
confidence: 99%